Torsion action and its possible observables - Belyaev, A. S. [UNESP]; Shapiro, I. L. [UNESP] (Elsevier, 1999)
The methods of effective field theory are used to explore the theoretical and phenomenological aspects of the torsion field. The spinor action coupled to the electromagnetic field and torsion possesses an additional softly broken gauge symmetry. This symmetry enables one to derive the unique form of the torsion action compatible with unitarity and renormalizability. It turns out that the antisymmetric torsion field is equivalent to a massive axial vector field. The introduction of scalars leads to serious problems which are revealed after the calculation of the leading two-loop divergences. Thus the phenomenological aspects of torsion may be studied only for the fermion-torsion systems. In this part of the paper we obtain upper bounds for the torsion parameters using present experimental data on forward-backward Z-pole asymmetries, data on the experimental limits on four-fermion contact interaction (LEP, HERA, SLAC, SLD, CCFR) and also TEVATRON limits on the cross section of a new gauge boson, which could be produced as a resonance at high energy pp collisions. The present experimental data enable one to put limits on the torsion parameters for the various ranges of the torsion mass. We emphasize that for a torsion mass of the order of the Planck mass no independent theory for torsion is possible, and one must directly use string theory. © 1999 Elsevier Science B.V.